The Reflection of Magneto-Thermoelastic $P$ and $SV$ Waves at a Solid Half Space Using Dual-Phase-Lag Model (Advances in Applied Mathematics and Mechanics, 2021)
The dual-phase-lag heat transfer model is employed to study the reflectionphenomena of $P$ and $SV$ waves from a surface of a semi-infinitemagneto-thermoelastic solid. The ratios of reflection coefficients to thatof incident coefficients are obtained for $P$- and $SV$-wave cases. Theresults for partition of the energy for various values of the angle ofincidence are computed numerically under the stress-free and rigidly fixedthermally insulated boundaries. The reflection coefficients are depending onthe angle of incidence, magnetic field, phase lags and other materialconstants. Results show that the sum of energy ratios is unity at theinterface. The results are discussed and depicted graphically.